2023
DOI: 10.1002/advs.202205146
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing of Humidity‐Driven Seed Inspired Soft Robots

Abstract: Geraniaceae seeds represent a role model in soft robotics thanks to their ability to move autonomously across and into the soil driven by humidity changes. The secret behind their mobility and adaptivity is embodied in the hierarchical structures and anatomical features of the biological hygroscopic tissues, geometrically designed to be selectively responsive to environmental humidity. Following a bioinspired approach, the internal structure and biomechanics of Pelargonium appendiculatum (L.f.) Willd seeds are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…[ 54 ] Finally, the proposed technology could be used to also develop energy harvesting applications based on photomechanical effects [ 55 ] stimulated by daily environmental variations, as well as bioinspired systems for environmental exploration, including, e.g., artificial seeds able to adaptively explore soils. [ 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 54 ] Finally, the proposed technology could be used to also develop energy harvesting applications based on photomechanical effects [ 55 ] stimulated by daily environmental variations, as well as bioinspired systems for environmental exploration, including, e.g., artificial seeds able to adaptively explore soils. [ 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…[377][378][379] These polymers offer fascinating dynamic and biomimetic responses, which permit them to develop structures for sensors, soft robots, artificial muscles, and smart electronic devices. [291,[380][381][382] 3D printing of humidity-responsive polymers enables the development of intricate and programmable structures. [383][384][385] Sometimes, humidity-responsive polymers are designed to enhance the mechanical properties of 3D-printed structures.…”
Section: Humidity-responsive Polymersmentioning
confidence: 99%
“…[530][531][532][533] Recent studies showed the development of smart grippers, actuators, and robots for different applications. [534][535][536][537][538][539][540] For instance, Cecchini et al [381] exploited the reshaping ability of humidityresponsive materials to develop a seed-like soft robot by using FDM printing, as illustrated in Figure 17A. In this approach, PCL-based filament were used to print a passive layer and electrospun cellulose nanocrystals (CNCs)/polyethylene oxide (PEO)based was used as an active layer to develop bilayer hygroscopic structures.…”
Section: Soft Roboticsmentioning
confidence: 99%
See 2 more Smart Citations